Seismic reflectivity effects from seasonal seafloor temperature variation. Issue 19 (9th October 2014) - Wood, Warren T.; Martin, Kylara M.; Jung, Wooyeol; Sample, John
Abstract The effects of seasonal temperature variation on sound speed contrasts at the seafloor are usually considered negligible in the analysis of seismic data but may be significant at large incidence angles (offsets) important for inversion of sediment elastic properties, or long‐range acoustic transmission. In coastal areas, the maximum annual seafloor temperature variation can be several degrees Celsius or more, corresponding to a sound speed variation of 30 m/s or more. Thermal pulses propagate via conduction several meters into the seafloor resulting in a damped quasi‐sinusoidal temperature profile with predictable wave number characteristics. The oscillating seasonal and spatial character of this signal creates a time‐ and frequency‐dependent effect on the elastic seafloor reflectivity. Results of numerical simulations show that the expected temperature profile for most sediment types and porosities will have the strongest affect on frequencies between about 60 and 600 Hz, at incidence angles greater than about 50°.